New insight on Carboniferous (Viséan) brachiopods from eastern Tafilalt (Morocco). (16th December 2015) - Mottequin, Bernard; Aretz, Markus; Herbig, Hans‐Georg; Baidder, Lahssen; Kaoukaya, Abdelhadi; Denayer, Julien
Abstract: Late Viséan brachiopods from the eastern Tafilalt (Morocco), and more precisely from the area comprised between the Jebel Begaa to the southwest, and Gara El Itima to the northeast (close to the Algerian border), are described systematically for the first time. Despite the limited material available, 18 species belonging to 17 genera have been recognized within the limestone beds of the Merdani and Zrigat formations, in which the productides (Productidina) and spiriferides are the most diverse. Representatives of the subfamily Gigantoproductidinae, which are close, if not conspecific, to those present in contemporaneous rocks of the nearby Béchar Basin (Algeria), occur in the late Viséan Zrigat Formation. Additional research based on more abundant material is necessary to investigate thoroughly the relationships existing between the Béchar Basin and the Tafilalt, which may have been part of the former during the Carboniferous. Copyright © 2015 John Wiley & Sons, Ltd.